2011
DOI: 10.1177/0886260511416468
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations Among Borderline Personality Disorder Symptoms, Interpersonal Problems, and Aggressive Behaviors

Abstract: This study examined the prospective relationships among borderline personality disorder (BPD) symptoms, interpersonal problems, and types of aggressive behaviors (i.e., experiencing psychological and physical victimization and perpetrating psychological and physical aggression) in a psychiatric sample (N = 139) over the course of 2 years. We controlled for other PD symptoms and demographic variables. BPD symptoms at baseline were associated with interpersonal sensitivity, interpersonal ambivalence, interperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 53 publications
6
38
1
1
Order By: Relevance
“…Long-term symptomatic ameliorations are related with interpersonal variables (quality of the relationship with partner or parents) [51]. Stepp et al [52] found that interpersonal problems mediated the relationship between BPD and later violent behaviors. The interpersonal difficulties of BPD patients are of vital relevance in general psychiatric hospitals; hospitalized BPD patients feel hostilely repulsed by staff members and affronted by other patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term symptomatic ameliorations are related with interpersonal variables (quality of the relationship with partner or parents) [51]. Stepp et al [52] found that interpersonal problems mediated the relationship between BPD and later violent behaviors. The interpersonal difficulties of BPD patients are of vital relevance in general psychiatric hospitals; hospitalized BPD patients feel hostilely repulsed by staff members and affronted by other patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Within their romantic relationships, various cross-sectional studies have reported that the partners of people with borderline personality disorder or traits are more likely to be subjected to physical and verbal hostility than the partners of people with other personality disorders [15,74,75] . Also, a 4-month follow-up study found that 37% of the partners of people with borderline personality were victims of their partner's physical or psychological violence [67] .…”
Section: Clinical Characteristics Of People With Borderline Personalimentioning
confidence: 99%
“…Hostility by the Partners of People with Borderline Personality Within their romantic relationships, several studies reported that the perception of domestic abuse by BPD women was higher than that observed among women without BPD [7,15] . Because of this, people with BPD or BPD traits are at great risk of revictimisation; that is, reliving childhood trauma through their adult romantic relationships [15,74,77] .…”
Section: Characteristics Of the Partners Of People With Borderline Pementioning
confidence: 99%
See 2 more Smart Citations